Carnegie Endowment for International Peace / Edited by James Brown Scott. - Scott, James Brown; Carnegie Endowment for International Peace (New York : The Endowment, 1917)
This website provides access to two types of research papers produced at the Carnegie Endowment for International Peace. More than forty policy briefs describe how various world problems affect U.S. interests. Also, more than sixty scholarly papers on international relations cover major issues affecting political, military, and economic relations around the globe.
Includes bibliographical references and index.
Keywords: International relations; Globalization; United States -- Foreign relations; United States military relations -- United States economic relations